Sintered flux of 3.5 Ni low-temperature steel and production method of sintered flux

By preparing a specific component sintered flux, the problems of hydrogen aggregation and stress cracking of 3.5Ni low-temperature steel under low temperature conditions were solved, and the arc stability, beauty of welding beads and free defects were achieved during welding.

CN119703491APending Publication Date: 2025-03-28SHANGHAI ATLANTIC WELDING CONSUMABLES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411934752.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

3.5Ni low-temperature steel is prone to the risk of hydrogen accumulation and stress cracking under low temperature conditions, resulting in welding defects and equipment safety hazards.

Method used

A sintering flux is used, and the raw materials are 3.4% to 21.5%, kaolin 19.9% ​​to 25.4%, silicon slurry 12.2% to 19.2%, fluorite 30.4% to 38.2%, sodium feldspar 6.5% to 12.5%, and ferrosilicate 0.2% to 0.8% respectively, and is prepared by specific mixing, stirring, low-temperature baking and high-temperature sintering steps to form a flux with excellent welding performance.

Benefits of technology

During the submerged arc welding process of 3.5Ni low-temperature steel, the arc is stable, the weld beads and the base material, and the weld beads are well fused, the slag removal is easy, the surface of the weld beads is beautifully formed, the edges of the weld are neat, and there are no defects such as edges, pores, and cracks, which effectively reduces the risk of hydrogen-induced cracks and obtains high-quality welds that match 3.5Ni low-temperature steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of welding materials, and discloses a sintered flux of 3.5 Ni low-temperature steel and a production method of the sintered flux. The sintered flux is prepared from, by weight, 3.4%-21.5% of magnesite, 19.9%-25.4% of kaolin, 12.2%-19.2% of silicon sludge, 30.4%-38.2% of fluorite, 6.5%-12.5% of albite and 0.2%-0.8% of silicon iron. The production method comprises the following steps: S1, weighing the raw materials in proportion, and uniformly mixing the raw material components; s2, adding 3.1 model potassium-sodium water glass with the concentration of 38%-42% and the total amount of the components being 18%-21% into the mixture in the step S1, uniformly stirring and granulating; s3, the particles obtained in the step S2 are baked at the low temperature of 200-230 DEG C for 40 min; s4, screening the particles baked in the step S2 by adopting a 10-mesh screen and a 40-mesh screen, and screening out particles except 10-40 meshes; and S5, the particles screened in the step S4 are sintered at the high temperature of 740-780 DEG C for 40 min, and after fine particles are screened out through a screen, the welding flux is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of welding materials, and more specifically, to a sintering flux for 3.5Ni low-temperature steel and a production method thereof. Background Art

[0002] 3.5Ni low-temperature steel is widely used in the manufacture of low-temperature equipment for ethylene, liquefied petroleum gas, fertilizer, rubber and coal gas projects, and its minimum operating temperature is %~101℃. By strictly controlling the content of impurity elements in the steel or adding some alloying elements, the purpose of solid solution strengthening and grain refinement can be achieved, and the grains can be refined by normalizing or normalizing + tempering treatment to make the structure uniform or have a face-centered cubic lattice, so that the steel has sufficient low-temperature toughness and the ability to resist brittle failure at low temperatures to ensure the safe operation of the equipment under low-temperature conditions. However, due to the increase in the bonding strength between the alloying elements and H atoms in the steel at low temperatures, hydrogen atoms gather in the steel, forming local brittle areas in the structure, thereby causing the risk of stress cracking. Summary of the invention

[0003] In order to overcome the deficiencies of the prior art, the present invention provides a sintering flux for 3.5Ni low-temperature steel and a production method thereof, which has the advantage of more precise operation.

[0004] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a sintering flux for 3.5Ni low-temperature steel, wherein the raw materials are respectively as follows in weight percentage: 3.4% to 21.5% of magnesite, 19.9% ​​to 25.4% of kaolin, 12.2% to 19.2% of silica mud, 30.4% to 38.2% of fluorite, 6.5% to 12.5% ​​of albite, and 0.2% to 0.8% of ferrosilicon.

[0005] As a preferred technical solution of the present invention, the raw materials are respectively as follows in weight percentage: 13.4% magnesite, 23% kaolin, 15.5% silica mud, 38.2% fluorite, 9.5% albite, and 0.4% ferrosilicon.

[0006] As a preferred technical solution of the present invention, the raw materials are respectively as follows in weight percentage: 16.8% magnesite, 25.4% kaolin, 12.2% silica mud, 36.9% fluorite, 8.5% albite, and 0.2% ferrosilicon.

[0007] As a preferred technical solution of the present invention, the raw materials are respectively as follows in weight percentage: 15.4% magnesite, 24% kaolin, 13.3% silica mud, 34% fluorite, 12.5% ​​albite, and 0.8% ferrosilicon.

[0008] As a preferred technical solution of the present invention, the raw materials are respectively as follows in weight percentage: 21.5% magnesite, 19.9% ​​kaolin, 17.5% silica mud, 34% fluorite, 6.5% albite, and 0.6% ferrosilicon.

[0009] As a preferred technical solution of the present invention, the raw materials are respectively as follows in weight percentage: 20.2% magnesite, 20.3% kaolin, 15.7% silica mud, 32.4% fluorite, 11.1% albite, and 0.3% ferrosilicon.

[0010] As a preferred technical solution of the present invention, the raw materials are respectively as follows in weight percentage: 17.6% magnesite, 22% kaolin, 19.2% silica mud, 30.4% fluorite, 10.5% albite, and 0.3% ferrosilicon.

[0011] As a preferred technical solution of the present invention, the present invention also discloses a method for producing a sintered flux for 3.5Ni low temperature steel, comprising the following steps:

[0012] S1. Weigh each raw material in proportion and mix each raw material component evenly;

[0013] S2, adding 3.1 modulus potassium sodium water glass with a total component amount of 18% to 21% and a concentration of 38% to 42% to the mixture of step S1, stirring evenly and granulating;

[0014] S3, baking the particles obtained in step S2 at a low temperature of 200° C. to 230° C. for 40 min;

[0015] S4, screening the particles baked in step S2 using a 10-mesh sieve and a 40-mesh sieve to remove particles other than 10-40 mesh;

[0016] S5, sintering the particles screened in step S4 at a high temperature of 740° C. to 780° C. for 40 min, and screening out finer particles with a sieve to obtain the flux;

[0017] The basicity of the flux is 3.2-3.6, and the bulkiness of the flux is 0.8-1.2 kg / m 3 .

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: the flux obtained by the present invention is used in combination with 3.5Ni low-temperature steel submerged arc welding wire for welding, the arc is stable, the weld bead and the base material, the weld bead and the weld bead are well fused, the slag is easy to remove, the weld bead surface is beautifully formed, the weld edge is neat, there are no welding defects such as undercut, pores, cracks, etc., S, H, and P are effectively removed, and a high-quality weld matching the 3.5Ni low-temperature steel is obtained. DETAILED DESCRIPTION

[0020] According to the composition range of the flux in the present invention and the method for preparing the flux in the present invention, the component contents shown in the table below are taken, and the flux is prepared according to the method described in Examples 1-6 described below, and a comparative example is prepared.

[0021] Magnesite Kaolin Silicon mud fluorite Sodium feldspar Ferrosilicon Example 1 13.4 23 15.5 38.2 9.5 0.4 Example 2 16.8 25.4 12.2 36.9 8.5 0.2 Example 3 15.4 24 13.3 34 12.5 0.8 Example 4 21.5 19.9 17.5 34 6.5 0.6 Example 5 20.2 20.3 15.7 32.4 11.1 0.3 Example 6 17.6 22 19.2 30.4 10.5 0.3 Comparative Example 25 32 11 24 6.8 1.2

[0022] Embodiment 1:

[0023] According to the component contents of Example 1 in the above table, the raw materials are placed in a mixer, stirred and mixed evenly, and then 3.1 mole potassium sodium water glass with a concentration of 39% and accounting for about 21% of the total weight of the powder is added and stirred and mixed, so that various powdery raw materials are mixed to form particles, granulated, and then baked at a low temperature of 200° C. to 230° C., sintered at a high temperature of 740° C. to 780° C., and sieved to obtain Flux No. 1.

[0024] Embodiment 2:

[0025] According to the component contents of Example 2 in the above table, the raw materials were placed in a mixer, stirred and mixed evenly, and then 3.1 mole potassium sodium water glass accounting for about 20% of the total weight of the powder and having a concentration of 42% was added and stirred, and granulated. The obtained granules were baked at a low temperature of 200° C. to 230° C., sintered at a high temperature of 740° C. to 780° C., and sieved to obtain flux No. 2.

[0026] Embodiment 3:

[0027] According to the component contents of Example 3 in the above table, the raw materials are placed in a mixer, stirred and mixed evenly, and then 3.1 modulus potassium sodium water glass with a concentration of 38% accounting for about 18% of the total weight of the powder is added, stirred and granulated, and then baked at a low temperature of 200°C to 230°C, sintered at a high temperature of 740°C to 780°C, and sieved to obtain Flux No. 3.

[0028] Embodiment 4:

[0029] According to the component contents of Example 4 in the above table, the raw materials are placed in a mixer, stirred and mixed evenly, and then 3.1 modulus potassium sodium water glass with a concentration of 41% accounting for about 19% of the total weight of the powder is added, stirred and granulated, and then baked at a low temperature of 200°C to 230°C, sintered at a high temperature of 740°C to 780°C, and sieved to obtain Flux No. 4.

[0030] Embodiment 5:

[0031] According to the component contents of Example 5 in the above table, the raw materials are placed in a mixer, stirred and mixed evenly, and then 3.1 modulus potassium sodium water glass with a concentration of 40% accounting for about 19% of the total weight of the powder is added, stirred and granulated, and then baked at a low temperature of 200°C to 230°C, sintered at a high temperature of 740°C to 780°C, and sieved to obtain Flux No. 5.

[0032] Embodiment 6:

[0033] According to the component contents of Example 6 in the above table, the raw materials are placed in a mixer, stirred and mixed evenly, and then 3.1 modulus potassium sodium water glass with a concentration of 39% accounting for about 20% of the total weight of the powder is added, stirred and granulated, and then baked at a low temperature of 200°C to 230°C, sintered at a high temperature of 740°C to 780°C, and sieved to obtain Flux No. 6.

[0034] Comparative Example:

[0035] According to the component contents of the comparative example in the above table, each raw material is placed in a mixer, stirred and mixed evenly, and then 3.1 modulus potassium sodium water glass with a concentration of 39% accounting for about 19% of the total weight of the powder is added, stirred and granulated, and then baked at a low temperature of 200°C to 230°C, sintered at a high temperature of 740°C to 780°C, and sieved to obtain a comparative flux.

[0036] experiment:

[0037] The test plate is a 25mm thick Q345 common steel plate, and a 3.5Ni low temperature steel special welding rod is used for the edge stacking. The flux prepared in the above embodiments 1-6 is matched with a 3.5Ni special submerged arc welding wire (Φ4.0mm) for welding test, with a welding current of 480-500A, an arc voltage of 30-32V, a welding speed of 22-25m / h36.7cm / min-41.6cm / min, an interpass temperature of less than 150°C, and a line energy of 20.8-26.2kJ / cm. After welding, a heat treatment of 930°C×40min air cooling+560°C×6h is performed; the special welding wire composition is calculated by weight percentage as follows: C: 0.07%, Mn: 0.82%, Si 0.16%, S 0.003%, P 0.005%, Cr0.08%, Ni3.48%, Cu 0.06%, and the balance is Fe.

[0038] The flux prepared in Examples 1-6 has excellent welding process, easy slag removal, beautiful weld formation, good straightness, and no defects such as pressure pits, slag inclusions, pores, and cracks.

[0039] The flux prepared in the comparative example has poor welding process: due to the high content of magnesite, the hardness of the slag shell is large, the surface corrugations of the weld are coarse and have sharp arcs, the slag removal is poor, and bulges and weld nodules appear when welding in the groove; when welding in the groove, the welding slag is not easy to break and is easily stuck in the groove, which makes the operation difficult and the welding efficiency low; the melting points of magnesite and kaolin are high, the slag removal of the flux is poor, the slag sticking is more serious, and slag inclusions are easy to occur, which is not conducive to operation; the ferrosilicon content is high, the silicon infiltration is more, and the weld metal impact is poor; the fluorite is insufficient, the [HF] partial pressure is too small, the molten pool is not fully protected, the arc environment air is easy to invade, resulting in an increase of [H][O][N], which is easy to cause hydrogen induced cracks, the test fails, and there are many pressure pits in the weld, affecting the use.

[0040] According to the relevant national testing standards, the performance of the welds was tested and the test results were shown in the following table:

[0041]

[0042] In the above table, tensile strength refers to the tensile strength of the welded joint, and diffusible hydrogen is the hydrogen content measured in the weld metal.

[0043] In the 6 groups of welding experiments described in this specification, the arc is stable, the slag removal is good, the weld performance is stable, the impact energy at -101°C is stable, the S, P, impurity content and diffusible hydrogen content are low, and the weld has good resistance to hydrogen-induced cracking.

[0044] The weld welded with the flux of the present invention has low S and P similar to the 3.5Ni low-temperature steel body, low diffusible hydrogen content, good -101°C low-temperature impact toughness and resistance to hydrogen-induced cracking, etc.; it is suitable for welding in the 3.5Ni low-temperature steel production environment, and obtains weld metal with beautiful weld shape and defects such as slag inclusion, pressure pits, and pores.

[0045] In the flux of the present invention, the magnesite refined by light burning and other methods has ultra-low S and P, and as a slag-forming agent, it is very important for the formation of slag and weld. However, due to the high melting point, the viscosity of the slag increases sharply during welding, the slag changes from long slag to short slag, and the melting temperature and solidification temperature of the slag increase, which inhibits the fluidity of the slag, resulting in poor weld formation, poor spreading, bulging in the center of the weld, hardening of the slag, and difficulty in slag removal. Therefore, it must be added together with materials such as silicon mud containing acidic oxides and reducing viscosity to effectively control the fluidity of the slag. In this application, the amount of magnesite added is controlled at 13.4% to 21.5%.

[0046] The SiO2 content in silicon mud is relatively high, about 90%, and the Al2O3 content is relatively low. Al2O3 can effectively adjust the slag removal of flux slag, has the effect of increasing the surface tension of slag, is an adjuster of slag viscosity, and improves the activity of slag. Through a large number of experimental comparisons, adding a certain amount of Al2O3 can reduce the tendency of pressure pits and the formation of pressure pits, but too high Al2O3 content will make the arc of the weld sharper and not smooth, easy to produce pores and pitting, and the slag shell will become hard. Too low content will make the weld surface uneven, and defects such as pressure pits and undercuts will appear, affecting the formation of the weld. The chemical composition of kaolin is 46.54% SiO2 and 39.5% Al2O3. In order to reasonably match MgO, SiO2, and Al 2O3, the addition amount of kaolin and silicon mud is controlled at 19.9% ​​to 25.4% and 12.2% to 19.2%.

[0047] Fluorite is the main material for reducing the diffusion hydrogen of the weld, which can increase the alkalinity of the flux, improve the toughness of the weld, effectively reduce the high-temperature viscosity of the slag, and improve the fluidity of the slag; fluorite is easy to ionize, and the F- generated by ionization can improve the conductivity of the arc, reduce the partial pressure of hydrogen in the arc atmosphere and the oxygen content in the deposited metal, which is beneficial to improve the low-temperature impact toughness of the weld metal. Adding 30.4% to 38.2% of fluorite to the flux of the present invention can play a role in stabilizing the arc.

[0048] Fluorite decomposes to produce CaO, and adding too much will easily cause the flux basicity to be too high, resulting in poor forming. In order to further reduce the diffusible hydrogen of the weld metal through the action of F ions, the present invention uses sodium fluoride to increase the amount of F ions added, and the sodium fluoride is controlled at 6.5-12.5%.

[0049] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0050] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A sintering flux for 3.5Ni low temperature steel, characterized in that: The raw materials are respectively as follows by weight percentage: 3.4% to 21.5% of magnesite, 19.9% ​​to 25.4% of kaolin, 12.2% to 19.2% of silica mud, 30.4% to 38.2% of fluorite, 6.5% to 12.5% ​​of albite, and 0.2% to 0.8% of ferrosilicon.

2. The sintering flux of 3.5Ni low temperature steel according to claim 1, characterized in that: The raw materials are respectively as follows in terms of weight percentage: 13.4% of magnesite, 23% of kaolin, 15.5% of silica mud, 38.2% of fluorite, 9.5% of albite and 0.4% of ferrosilicon.

3. The sintering flux of 3.5Ni low temperature steel according to claim 1, characterized in that: The raw materials are respectively as follows in terms of weight percentage: 16.8% of magnesite, 25.4% of kaolin, 12.2% of silica mud, 36.9% of fluorite, 8.5% of albite and 0.2% of ferrosilicon.

4. The sintering flux for 3.5Ni low temperature steel according to claim 1, characterized in that: The raw materials are respectively as follows in terms of weight percentage: 15.4% of magnesite, 24% of kaolin, 13.3% of silica mud, 34% of fluorite, 12.5% ​​of albite and 0.8% of ferrosilicon.

5. The sintering flux for 3.5Ni low temperature steel according to claim 1, characterized in that: The raw materials are respectively as follows in terms of weight percentage: 21.5% of magnesite, 19.9% ​​of kaolin, 17.5% of silica mud, 34% of fluorite, 6.5% of albite and 0.6% of ferrosilicon.

6. The sintering flux for 3.5Ni low temperature steel according to claim 1, characterized in that: The raw materials are respectively as follows in terms of weight percentage: 20.2% of magnesite, 20.3% of kaolin, 15.7% of silica mud, 32.4% of fluorite, 11.1% of albite and 0.3% of ferrosilicon.

7. The sintering flux for 3.5Ni low temperature steel according to claim 1, characterized in that: The raw materials are respectively as follows in terms of weight percentage: 17.6% of magnesite, 22% of kaolin, 19.2% of silica mud, 30.4% of fluorite, 10.5% of albite and 0.3% of ferrosilicon.

8. The method for producing a sintered flux for 3.5Ni low temperature steel according to any one of claims 1 to 7, characterized in that: The steps include: S1. Weigh each raw material in proportion and mix each raw material component evenly; S2, adding 3.1 modulus potassium sodium water glass with a total component amount of 18% to 21% and a concentration of 38% to 42% to the mixture of step S1, stirring evenly and granulating; S3, baking the particles obtained in step S2 at a low temperature of 200° C. to 230° C. for 40 min; S4, screening the particles baked in step S2 using a 10-mesh sieve and a 40-mesh sieve to remove particles other than 10-40 mesh; S5, sintering the particles screened in step S4 at a high temperature of 740° C. to 780° C. for 40 min, and screening out finer particles with a sieve to obtain the flux; The basicity of the flux is 3.2-3.6, and the bulkiness of the flux is 0.8-1.2 kg / m 3 .